To test or not to test: preliminary assessment of normality when comparing two independent samples - Rochon, Justine; Gondan, Matthias; Kieser, Meinhard (BMC medical research methodology, 2012)
Student’s two-sample t test is generally used for comparing the means of two independent samples, for example, two treatment arms. Under the null hypothesis, the t test assumes that the two samples arise from the same normally distributed population with unknown variance. Adequate control of the Type I error requires that the normality assumption holds, which is often examined by means of a preliminary Shapiro-Wilk test. The following two-stage procedure is widely accepted: If the preliminary test for normality is not significant, the t test is used; if the preliminary test rejects the null hypothesis of normality, a nonparametric test is applied in the main analysis.
Gesehen am 16.07.2018